Comparing the incidence of anterior cruciate ligament injury in collegiate lacrosse, soccer, and basketball players - Mihata, L. C. S.; Beutler, A. I.; Boden, B. P. (The American Journal of Sports Medicine, 2006)
Female college basketball and soccer athletes have higher rates of anterior cruciate ligament injury than do their male counterparts. Rates of anterior cruciate ligament injuries for women and men in collegiate lacrosse have not been examined. Understanding anterior cruciate ligament injury patterns in lacrosse, a full-contact sport for men and noncontact sport for women, could further injury prevention efforts.